Bayesian methods in economics and finance: Editor's introduction - Jun YU (Institutional Knowledge at Singapore Management University, 2022)
Modern days, Bayesian methods have gained prominence in theoretical work and applications in economics and finance due to the rapid development of computational technologies and their ability to learn. The special issue intends to examine central aspects in Bayesian analysis and applications, including prior choices, model selection with massive data and latent variables, hypothesis testing, Bayesian learning. In total, this special issue contains ten papers, all subject to the Journal of Econometrics (JOE)’s normal refereeing process. Most of these papers came from a conference held at the ESSEC Singapore campus on 10 December 2018.